End‐binding protein 1 (EB1) up‐regulation is an early event in colorectal carcinogenesis. Issue 5 (1st February 2014) - Stypula-Cyrus, Yolanda; Mutyal, Nikhil N.; Dela Cruz, Mart; Kunte, Dhananjay P.; Radosevich, Andrew J.; Wali, Ramesh; Roy, Hemant K.; Backman, Vadim
Abstract : End‐binding protein (EB1) is a microtubule protein that binds to the tumor suppressor adenomatous polyposis coli (APC). While EB1 is implicated as a potential oncogene, its role in cancer progression is unknown. Therefore, we analyzed EB1/APC expression at the earliest stages of colorectal carcinogenesis and in the uninvolved mucosa ("field effect") of human and animal tissue. We also performed siRNA‐knockdown in colon cancer cell lines. EB1 is up‐regulated in early and field carcinogenesis in the colon, and the cellular/nano‐architectural effect of EB1 knockdown depended on the genetic context. Thus, dysregulation of EB1 is an important early event in colon carcinogenesis. Abstract : EB1 expression is significantly increased in early and field carcinogenesis in the colon. Knockdown of EB1 reduced the cancerous phenotype in colon cancer cell lines. LEBS analysis of EB1 knockdown cells shows distinct changes in cell nano‐architecture.